The second wave reflections on the pandemic through photography, performance and public culture - Bharucha, Rustom 1953- (Calcutta, India Seagull Books, 2022)
"Focusing on the second wave of the Covid-19 pandemic in India between April and December 2021, Rustom Bharucha's timely essay reflects on four interconnected realities that haunted this ongoing crisis -- death, grief, mourning, and extinction. How do we cope with multiple deaths and the dislocation of rituals when the act of mourning is either postponed or denied? What roles do political surveillance, censorship, the regulation of lockdowns, and the sheer indifference to the lives of people play in the containment of civil liberties? Through vivid examples of photography, theater, dance, visual arts, and the cultures of everyday life, this meditative essay illuminates both the horror of the pandemic as well as its unexpected intimacies and revelations of shared suffering. Against the destruction of nature and the disrespect for the nonhuman, The Second Wave offers lessons in resilience through its reflections on the ethos of waiting and the need to re-envision breath as a vital resource of self-renewal and resistance."--back cover.
Includes bibliographical references (pages 204-216).
AL-2501 donated by UP DSCTA
Keywords: Art and society; COVID-19 Pandemic, 2020-2023, in art; Suffering in art; Art and society -- India -- 21st Century